1994
DOI: 10.1007/bf00124888
|View full text |Cite
|
Sign up to set email alerts
|

The immediate effects of ionomeric and acrylic bone cements on peripheral nerve function

Abstract: A total of 44 rat saphenous nerves were isolated. A pair of stimulating electrodes was positioned distally (at the ankle) to evoke a compound action potential (CAP) which was recorded proximally (in the thigh) through another pair of electrodes. Bone cement was then placed adjacent to the nerve midway between the electrodes and changes in the CAP recorded over a 30-min period. Nerve conduction was completely blocked within 2 min of placing unset acrylic bone cement adjacent to the nerve. The experimental ionom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
2
3
1
Order By: Relevance
“…We previously reported that partially set IC had no effect on nerve conduction for over 10 min, whereas acrylic caused conduction block within 2 min [1]. Together with the results from the present specially designed animal experiments, this suggests that if polyalkenoate acid is released from ionomeric cements during gelation it is slow to diffuse through the connective tissues compared with methylmethacrylate monomer.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…We previously reported that partially set IC had no effect on nerve conduction for over 10 min, whereas acrylic caused conduction block within 2 min [1]. Together with the results from the present specially designed animal experiments, this suggests that if polyalkenoate acid is released from ionomeric cements during gelation it is slow to diffuse through the connective tissues compared with methylmethacrylate monomer.…”
Section: Discussionsupporting
confidence: 70%
“…In a previous study we demonstrated that neural conduction is blocked within two minutes of placing acrylic cement adjacent to a peripheral nerve [1]. We have also confirmed that if the acrylic is applied in the same way as described in the present experiments, rapid block of nerve conduction occurs.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…At this time, however, a number of concerns were raised over the in vivo neurotoxicity of the setting cement. 8,9 Serious adverse events were subsequently reported including death following skull base surgery where relatively large volumes of ionomer bone cement were placed in direct contact with cerebral spinal fluid (CSF) or brain tissue. [10][11][12] While doubts have been since expressed over the surgical approach taken, and current glass ionomer bone cements are now contra-indicated for these clinical applications and concerns remain regarding the biocompatibility of these biomaterials.…”
Section: Introductionmentioning
confidence: 99%